Efficacy of Pheromone on Capturing Angoumois Grain Moth (Sitotroga Cerealella) in Stored Rice (Oryza Sativa L.) Grain (The Agriculturists, 2016)
An experiment on the efficacy of pheromone on capturing angoumois grain moth, Sitotroga cerealella (Olivier) was conducted in the laboratory of the Department of Entomology, Sher-e-Bangla Agricultural University, Bangladesh, using rice variety BR11. Pheromone (X-lure) trap was used as a treatment and data were recorded at different days and distances. The experiment was laid out in a Completely Randomized Design (CRD) with four replications. In case of total captured moth, the highest percentage (%) was recorded at 1st day (28.60%), whereas the lowest percentage (%) was recorded at 15th day (7.60%). It was also observed that with the increase of distance of pheromone trap, the % of captured moth was decreased. The pheromone X-lure was found useful only for monitoring S. cerealella (Olivier).The Agriculturists 2015; 13(2) 74-80